A new Upper Triassic cynodont-bearing fossiliferous site from southern Brazil, with taphonomic remarks and description of a new traversodontid taxon. (December 2018) - Pavanatto, Ane Elise Branco; Pretto, Flávio Augusto; Kerber, Leonardo; Müller, Rodrigo Temp; Da-Rosa, Átila Augusto Stock; Dias-da-Silva, Sérgio
Abstract: A new Upper Triassic fossiliferous outcrop, the Niemeyer Site, from the Santa Maria Supersequence (Paraná Basin, Southern Brazil) is reported. The lithology found in this locality is consistent with that found in the Candelária Sequence. The high prevalence of traversodontid cynodonts in this site is particularly notable, with collected specimens mostly composed of isolated bones and fragmentary specimens, but also including well-preserved skulls and mandibles. Probainognathian cynodonts and archosauromorphs are also present, but they are rare in comparison. There is a predominance of Voorhies Group III (Group III > Group I > Group II) for the specimens so far collected. These data, as well as the sedimentary data of the outcrop, indicate a mostly autochthonous fossiliferous assemblage. Some specimens display evidence of ichnological activity of invertebrate scavengers (bone alteration comprising small tubules, channels and isolated boreholes). A remarkable aspect of this site is the presence of a new traversodontid cynodont closely related to Exaeretodon . Although similar to the former taxon, the new taxonomic unit shows a unique combination of several craniodental features not present in other cynodonts. Given that no traversodontids are recorded in the uppermost levels of the Candelária Sequence, this site is likely placed in the lower levels of this unit, with the fauna suggesting a Carnian age. Highlights: A new fossiliferous outcrop from the Upper Triassic of South America is described. The fossil content of this outcrop differs from the well-known Assemblage Zones of Santa Maria Supersequence. It is remarkable the high amount of traversodontid cynodonts. A new taxon of traversodontid cynodont, Siriusgnathus niemeyerorum, is described.